HIV-2 drug resistance genotyping and viral load among HIV-2 infected adults in Burkina Faso, West Africa: HIV-2 drug resistance and viral load - Soubeiga, Serge Theophile; Yonli, Albert Theophane; Senghor, Ngardjibem Madjitoudjoum; Nantchouang, Alain; Simpore, Jacques (Cellular and Molecular Biology, 2024)
HIV-2 infection although less virulent compared to HIV-1 is endemic in many parts of West Africa. In Burkina Faso, few data exist on HIV-2 genotypic resistance. The objective of this study was to assess HIV-2 genotypic resistance and viral load in adult patients infected with HIV-2 in Burkina Faso. This was a cross-sectional study that ran from February 2017 to March 2019. This study included 91 HIV-infected adult patients on ARV treatment. HIV and hepatitis B and C status were confirmed by serological tests. HIV-2 viral load and HIV-2 clusters were determined by in-house tests. The mean age was 58.99 ±8.66 years. Of the patients, 12.1% were HIV-1, 73.6% were HIV-2 and 14.3% were co-infected with HIV-1/HIV-2. Only 15% had a high viral load (more than 1000 copies/mL). Groups A and B were detected in this study with the majority being group A (23.75%). HIV-2 subtype CRF01_AB was found in 3.75% of HIV-2 patients. Of the 34 HIV-2 patients whose subtypes were determined, only 7 had reverse transcriptase and 3 had protease resistance mutations. The M184V mutation was the most detected. This study revealed recent data on the status of HIV-2 genotypic resistance in Burkina Faso. Although few HIV-2 infected patients on ARV treatment have developed resistance, it is important to establish a surveillance system for HIV-2 genotypic resistance.